The ‘PAI-1 paradox’ in vascular remodelling - Diebold, Isabel; Kraicun, Damir; Bonello, Steve; Görlach, Agnes (Thrombosis and Haemostasis, 2008)
Vascular remodelling isa complex phenomenon associated with restructuring of the vessel wall as a consequence of disruption of vascular homeostasis. Alterations of the vascular wall have been linked to a variety of cardiovascular disorders including atherosclerosis, vascular injury and pulmonary hypertension. Plasminogen activator inhibitor-1 (PAI-1) is a member of the serpin (serine proteinase inhibitor) family and acts as an important inhibitor of fibrinolysis by interfering with the plasminogen system. In addition to its anti-fibrinolytic effects, PAI-1 appears to modulate cellular responses linked to vascular remodelling. Since PAI-1 levels have been shown to be altered in various disorders associated with vascular remodelling of the systemic and pulmonary vascular bed, this serpin may playa pivotal role in the pathogenesis of these diseases.
Keywords: Plasminogen activator inhibitors; atherosclerosis; restenosis; remodelling; pulmonary hypertension